The Urgency of Learning English as an Effort to Introduce a Foreign Language to Elementary - Tiarnita Maria Sarjani Br. Siregar; Nur Kibah Mandasari; Siti Annisa; Iasyah Fakhrany (International Journal of Education, Information Technology, and Others, 2026)
This study is motivated by the urgency of English language learning in elementary schools amid the rapid development of globalization and technology, which increasingly demands early foreign language competence in young learners. The objective of this research is to analyze the importance of introducing English at an early age, identify supporting and inhibiting factors in its implementation, and formulate relevant pedagogical strategies to enhance student engagement and language skills. This research employed a qualitative approach using a literature study (library research) method by reviewing scientific journal articles, educational textbooks, and national education policy documents. Data were analyzed through content and descriptive analysis following the stages of data reduction, data display, and conclusion drawing. The findings indicate that the urgency of English learning in elementary schools is grounded in three main dimensions: biological-cognitive, referring to the golden period of language acquisition in which children absorb language more naturally and efficiently; socio-global, reflecting the demands of global competitiveness that require early exposure to international communication; and pedagogical, emphasizing the critical role of creative, contextual, and engaging learning strategies in fostering language development. Despite challenges such as limited teacher competence, inadequate learning media, and inconsistent curriculum implementation across regions, this study identifies several strategic solutions. These include strengthening national education policies, equalizing teacher quality through professional training, and implementing activity-based and play-based learning methods. It is concluded that an integrated and well-supported approach is essential to optimize English learning outcomes at the elementary school level and prepare students for the demands of the 21st century.